Altering physiological conditions and semen acidity by manipulating dietary cation-anion difference and fish oil supplemenation of Garut breed rams - Rahmat Hidayat; T. Toharmat; A. Boediono; I.G. Permana (Jurnal Ilmu Ternak dan Veteriner, 2009)
Contribution of Garut breed sheep as protein resources is not optimal yet.  Acceleration of population growth such as increasing of female offspring is neccesary.  This study was carried out to obtain information regarding the effect of dietary cation-anion difference (PKAR: meq [(Na + K) – (Cl+S)/100 g of dry matter]) and fish oil supplementation on acidity of blood and semen, blood gas and plasma and semen mineral. The dietary treatmens were as follows:   RN0= basal ration (PKAR +14) without fish oil, RNI= basal ration (PKAR +14) with 3% fish oil, RB0= base ration (PKAR +40) without fish oil, RBI= base ration (PKAR +40) with 3% fish oil, RA0= acid ration (PKAR -40) without fish oil, and RAI= acid ration (PKAR -40) with 3% fish oil.  The rations contained 150 ppm of zinc and were offered to 18 of Garut rams.  The result indicated that blood pH, pCO2, and pO2 were not affected by PKAR and fish oil supplementation, but cHCO3 and cBase were affected (P<0.05).  PKAR and fish oil supplementation affected (P<0.01) plasma Mg and S, but did not affect K, Na, Zn and Cl.  Semen pH after day 28 of experimental period were highly significant different and that followed PKAR pattern.  In conclution, PKAR affected cBase, cHCO3, concentration of Mg and S plasma and semen pH of Garut rams.  The result suggested that PKAR could be applied to manipulate physiological condition and semen pH. Key Words: PKAR, Physiological Condition, Semen, Garut Ram